Comorbid Psychiatric Disorders and Related Sociodemographic Factors in Adolescents with Attention-Deficit Hyperactivity Disorder - Serdar Karatoprak; Yunus Emre Dönmez (Galenos Publishing House, 2022)
Objective: Attention-deficit hyperactivity disorder (ADHD) disorder is a neuropsychiatric disorder that begins in early stages of life and has a lifelong effect. Previous studies have found that 50-70% of children and adolescents with ADHD have comorbid psychiatric disorders. The aim of this study is to identify comorbid psychiatric disorders in adolescents with ADHD and to compare the sociodemographic characteristics of ADHD cases with and without psychiatric comorbidity. Method: This study was conducted with 105 adolescents with ADHD. The Schedule for Affective Disorders and Schizophrenia for School-age Children-present and Lifetime-Turkish version was used to evaluate ADHD and comorbid psychiatric disorders. Results: The study was completed with 73 male and 32 female adolescents. The mean age of the participants was 13.75+-1.45 years. It was determined that 41 cases (39%) had at least one comorbid psychiatric disorder. The most common comorbid psychiatric disorders were conduct disorder (14.3%), specific learning disorder (8.6%), obsessive compulsive disorder (3.8%) and elimination disorders (3.8%). While the prevalence of comorbid psychiatric disorders was compared according to sociodemographic characteristics, it was found that the prevalence of comobidity was significantly higher in adolescents with ADHD living in families with low socioeconomic levels. Conclusion: The findings of current study showed that adolescents with ADHD had a high rate of comorbid psychiatric disorders. We are opinion that presence of comorbid psychiatric disorder in ADHD will have negative effects on both ADHD and comorbid psychiatric problems. Therefore, all adolescents with ADHD should be evaluated for comorbid psychiatric disorders.